Incidence Of Helicobacter Pylori Infection in Association With ABO Blood Groups - Amina Zehra; Maimoona Sabir; Sumaira Sarwar; Afsheen Ishfaq; Kishmain Ahmad; Afshan Saleem (Journal of Rawalpindi Medical College)
Objective: The study aimed to investigate the association between ABO blood groups and helicobacter infection.